Mountain runaways - Withers, Pam (Dundurn Press, 2022)
"When three siblings run away to hide in the mountains, they have to face search parties, hunger, injury -- and the danger of their team unravelling. First a Canadian Rockies avalanche kills their parents. Then Children's Services threatens to separate them. That's when the three Gunnarsson kids, Jon, Korka, and Aron, decide to run away into the mountains and fend for themselves until Jon turns eighteen and becomes their legal guardian. But can they survive all that the backcountry throws at them -- hunger, illness and injury, dangerous animals, a shadowy woods dweller, and search teams in pursuit? Above all, can they stop their feisty threesome from unravelling?"--